Cortico-Cortical Connectivity between Right Parietal and Bilateral Primary Motor Cortices during Imagined and Observed Actions: A Combined TMS/tDCS Study - Feurra, Matteo; Bianco, Giovanni; Polizzotto, Nicola R.; Innocenti, Iglis; Rossi, Alessandro; Rossi, Simone (Frontiers in Neural Circuits, 2011)
Previous TMS studies showed functional connections between the parietal cortex (PC) and the primary motor cortex (M1) during tasks of different reaching-to-grasp movements. Here, we tested whether the same network is involved in cognitive processes such as imagined or observed actions. Single pulse TMS of the right and left M1 during rest and during a motor imagery and an action observation task (i.e. an index-thumb pinch grip in both cases) was used to measure corticospinal excitability changes before and after conditioning of the right PC by 10 minutes of cathodal, anodal or sham transcranial direct current stimulation (tDCS). Corticospinal excitability was indexed by the size of motor evoked potentials (MEPs) from the contralateral FDI (target) and ADM (control) muscles. Results showed selective ipsilateral effects on the M1 excitability, exclusively for motor imagery processes: anodal tDCS enhanced the MEPs’ size from the FDI muscle, whereas cathodal tDCS decreased it. Only cathodal tDCS impacted corticospinal facilitation induced by action observation. Sham stimulation was always uneffective. These results suggest that motor imagery, differently from action observation, is sustained by a strictly ipsilateral parieto-motor cortex circuits. Results might have implication for neuromodulatory rehabilitative purposes.